First record and redescription of Binodoxys brevicornis (Hymenoptera: Braconidae: Aphidiinae) from Argentina - Zumoffen, Leticia (2013)
Binodoxys brevicornis (Haliday) is reported for the first time for Argentina. This aphidiine was found parasitizing the aphid Hyadaphis foeniculi (Passerini) feeding on Foeniculum vulgare (Miller), a non-crop plant species commonly occurring near alfalfa crops. Binodoxys brevicornis is redescribed and illustrated.